The INA complex facilitates assembly of the peripheral stalk of the mitochondrial F1Fo‐ATP synthase. (18th June 2014) - Lytovchenko, Oleksandr; Naumenko, Nataliia; Oeljeklaus, Silke; Schmidt, Bernhard; von der Malsburg, Karina; Deckers, Markus; Warscheid, Bettina; van der Laan, Martin; Rehling, Peter
Abstract Mitochondrial F1Fo‐ATP synthase generates the bulk of cellular ATP. This molecular machine assembles from nuclear‐ and mitochondria‐encoded subunits. Whereas chaperones for formation of the matrix‐exposed hexameric F1‐ATPase core domain have been identified, insight into how the nuclear‐encoded F1‐domain assembles with the membrane‐embedded Fo‐region is lacking. Here we identified the INA complex (INAC) in the inner membrane of mitochondria as an assembly factor involved in this process. Ina22 and Ina17 are INAC constituents that physically associate with the F1‐module and peripheral stalk, but not with the assembled F1Fo‐ATP synthase. Our analyses show that loss of Ina22 and Ina17 specifically impairs formation of the peripheral stalk that connects the catalytic F1‐module to the membrane embedded Fo‐domain. We conclude that INAC represents a matrix‐exposed inner membrane protein complex that facilitates peripheral stalk assembly and thus promotes a key step in the biogenesis of mitochondrial F1Fo‐ATP synthase.